Activation of AP-1 and of a nuclear redox factor, Ref-1, in the response of HT29 colon cancer cells to hypoxia. - Yao, K S (1994)
Many solid tumors contain substantial fractions of hypoxic cells which are relatively resistant to both radiation therapy and certain cytotoxic drugs. We have previously shown that exposure of human HT29 cells to hypoxic conditions results in the overexpression of certain enzymes involved in the detoxication of xenobiotics, including NAD(P)H:(quinone acceptor) oxidoreductase (DT)-diaphorase, and gamma-glutamylcysteine synthetase, the rate-limiting enzyme in glutathione synthesis. This hypoxic effect on DT-diaphorase was shown to involve both transcriptional induction and altered message stability. We have investigated the effects of hypoxia on elements in the promoter region of DT-diaphorase. Electrophoretic mobility shift assays demonstrate the induction of a binding activity to the AP-1 response element of DT-diaphorase. Supershift assays suggest that this binding is due to AP-1 nuclear factors and that members of the jun family are induced to a greater degree than fos by hypoxia. Analysis of the kinetics of transcription factor expression indicates that the expression of c-jun and junD is induced during hypoxic exposure; mRNA levels fall during reoxygenation. Induction of fos on the other hand is not as florid during hypoxia (5-fold) and is most pronounced (17-fold) 24 h after the restoration of an oxic environment. Thus, the hypoxic response of DT-diaphorase expression is mediated in part through AP-1, initially by a jun-related mechanism and then by the involvement of fos. The affinity of transcription factors for the AP-1 binding site depends on the redox state of a cysteine residue located close to the DNA-binding region of both Fos and Jun. A nuclear protein, Ref-1, maintains the reduced state of Fos and Jun and promotes binding to AP-1. Nuclear extracts of HT29 cells exposed to hypoxia show markedly increased Ref-1 protein content. Elevation of ref-1 steady-state mRNA levels occurs as an early event following induction of hypoxia and persists when cells are restored to a normally oxygenated environment. Nuclear run-on analysis demonstrates that induction of transcription is the mechanism of ref-1 mRNA elevation. Electrophoretic mobility shift assays and immunodepletion assays were used to further define the interaction of Ref-1 with specific AP-1-binding proteins under hypoxic conditions. These data demonstrate that the induction of detoxicating enzyme expression in HT29 cells exposed to hypoxia results from the induction of both transactivating factors that bind to the AP-1 element and of redox proteins that enhance their affinity for this element.